Tantalum and magnesium nanoparticles enhance the biomimetic properties and osteo-angiogenic effects of PCL membranes - Nan, Jiangyu; Liu, Wenbin; Zhang, Kai; Sun, Yan; Hu, Yihe; Lei, Pengfei (Frontiers in Bioengineering and Biotechnology, 2022)
Segmental bone defects, accompanied by periosteum stripping or injury, usually lead to delayed bone union or nonunion, which have challenged orthopedic surgeons. The periosteum, which provides essential blood supply and initial stem cells for bone tissue, plays an important role in the repair of bone defects. The reconstruction of the destroyed periosteum has attracted the attention of researchers exploring more satisfactory therapies to repair bone defects. However, periosteum-like biomaterials have yet to meet the clinical requirements and resolve this challenging problem. In this study, we manufactured a nanofiber periosteum replacement based on poly-ε-caprolactone (PCL), in which tantalum nanoparticles (TaNPs) and nanoscale magnesium oxide (MgO) were introduced to enhance its osteogenic and angiogenic ability. The results of in vitro experiments indicated that the PCL/Ta/MgO periosteum replacement, with excellent cytocompatibility, promoted the proliferation of both bone marrow mesenchymal stem cells (BMSCs) and endothelial progenitor cells (EPCs). Furthermore, the incorporation of TaNPs and nano-MgO synergistically enhanced the osteogenic differentiation of BMSCs and the angiogenic properties of EPCs. Similarly, the results of in vivo experiments from subcutaneous implantation and critical-sized calvarial defect models showed that the PCL/Ta/MgO periosteum replacement combined the osteogenesis and angiogenesis abilities, promoting vascularized bone formation to repair critical-sized calvarial defects. The results of our study suggest that the strategy of stimulating repairing bone defects can be achieved with the periosteum repaired in situ and that the proposed periosteum replacement can act as a bioactive medium to accelerate bone healing.